Antibacterial Activity of Alcoholic and Aqueous Extracts of Agaricus bisporus Against Food Borne Bacterial Pathogens - Hussein, Alyaa Razooqi; Ali, Eman Mohammed; Hamid, Ebtehal (Al-Nahrain Journal of Science, 2018)
Two extracts of 50 mg.ml-1 Agaricus bisporus alcoholic and aqueous were used in order to study their effect against two pathogenic bacteria. Salmonella typhi and Staphylococcus aureus strains isolated from chicken and minced meat samples respectively, then identified according to biochemical tests. Antibacterial activity of Agaricus bisporus extracts (alcoholic and aqueous) was studied by agar well diffusion method. The results exhibited that aqueous mushroom extract has no effect against the two tested bacteria, while alcoholic extract of mushroom affect against the two tested bacteria and the effect against S. aureus was more than that against Salmonella typhi and the zone of inhibition was 15 mm and 9 mm respectively. The ethanol alcohol 96% and water were used as control. From this study, mushroom extracts especially ethanolic or alcoholic could be used to control the transmission of pathogenic bacteria from food